Utilization of palauan (Cyrtosperma merkusii (Hassk) Schott) flour in the production of kroepeck - Celfo, Dinah Elumba (2003.)
Palauan (Cyrtosperma merkusii (Haskk) Schott.) is one of the indigenous root crops whose commercial value remains low because it is under utilized as food.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Palauan; Cyrtosperma merkusii (Haskk) Schott; Flour; Kroepeck